Impact of Active Disinvestment on Decision-Making for Surgery in Patients With Subacromial Pain Syndrome: A Qualitative Semi-structured Interview Study Among Hospital Sales Managers and Orthopedic Surgeons - Timon Geurkink; Perla J. Marang-van de Mheen; Jochem Nagels; Rudolf W. Poolman; Rob G.H.H. Nelissen; Leti van Bodegom-Vos (Kerman University of Medical Sciences, 2023)
Background  Withdrawal of reimbursement for low-value care through a policy change, ie, active disinvestment, is considered a potentially effective de-implementation strategy. However, previous studies have shown conflicting results and the mechanism through which active disinvestment may be effective is unclear. This study explored how the active disinvestment initiative regarding subacromial decompression (SAD) surgery for subacromial pain syndrome (SAPS) in the Netherlands influenced clinical decision-making around surgery, including the perspectives of orthopedic surgeonsand hospital sales managers.Methods  We performed 20 semi-structured interviews from November 2020 to October 2021 with ten hospital sales managers and ten orthopedic surgeons from twelve hospitals across the Netherlands as relevant stakeholders in the active disinvestment process. The interviews were video-recorded and transcribed verbatim. Inductive thematic analysis was used to analyse interview transcripts independently by two authors and discrepancies were resolved through discussion.Results  Two overarching themes were identified that negatively influenced the effect of the active disinvestment initiative for SAPS. The first theme was that the active disinvestment represented a "Too small piece of the pie" indicating little financial consequences for the hospital as it was merely used in negotiations with healthcare insurers to reduce costs, required a disproportionate amount of effort from hospital staff given the small saving-potential, and was not clearly defined nor enforced in the overall healthcare insurer agreements. The second theme was "They [healthcare insurer] got it wrong," as the evidence and guidelines had been incorrectly interpreted, the active disinvestment was at odds with clinician experiences and beliefs and was perceived as a reduction in their professional autonomy.Conclusion  The two overarching themes and their underlying factors highlight the complexity for active disinvestment initiatives to be effective. Future de-implementation initiatives including active disinvestment should engage relevant stakeholders at an early stage to incorporate their different perspectives, gain support and increase the probability of success.